Review of Epidural Spinal Cord Stimulation for Augmenting Cough after Spinal Cord Injury - Hachmann, Jan T.; Calvert, Jonathan S.; Grahn, Peter J.; Drubach, Dina I.; Lee, Kendall H.; Lavrov, Igor A. (Frontiers in Human Neuroscience, 2017)
Spinal cord injury (SCI) remains a debilitating condition for which there is no cure. In addition to loss of somatic sensorimotor functions, SCI is also commonly associated with impairment of autonomic function. Importantly, cough dysfunction due to paralysis of expiratory muscles in combination with respiratory insufficiency can render affected individuals vulnerable to respiratory morbidity. Failure to clear sputum can aggravate both risk for and severity of respiratory infections, accounting for frequent hospitalizations and even mortality. Recently, epidural stimulation of the lower thoracic spinal cord has been investigated as novel means for restoring cough by evoking expiratory muscle contraction to generate large positive airway pressures and expulsive air flow. This review discusses available preclinical and clinical evidence, current challenges, and clinical potential of lower thoracic spinal cord stimulation (SCS) for restoring cough in individuals with SCI.